2014
DOI: 10.7314/apjcp.2014.15.8.3451
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CEA Expression and EGFR Mutation Status in Non-small Cell Lung Cancers

Abstract: Background: The serum carcinoembryonic antigen (CEA) level can reflect tumor growth, recurrence and metastasis. It has been reported that epidermal growth factor receptor (EGFR) mutations in exons 19 and 21may have an important relationship with tumor cell sensitivity to EGFR -TKI therapy. In this study, we investigated the clinical value of EGFR mutations and serum CEA in patients with non-small cell lung cancer (NSCLC). Materials and Methods:The presence of mutations in EGFR exons 19 and 21 in the tissue sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
1
20
1
Order By: Relevance
“…15,[17][18][19] In this study, a CEA cut-off of 5 ng/mL was not found to be useful for distinguishing SCLC combined with adenocarcinoma from pure SCLC. This may be because most of our patients had a history of cigarette smoking, and serum CEA levels are known to be elevated in smokers.…”
Section: Discussioncontrasting
confidence: 59%
“…15,[17][18][19] In this study, a CEA cut-off of 5 ng/mL was not found to be useful for distinguishing SCLC combined with adenocarcinoma from pure SCLC. This may be because most of our patients had a history of cigarette smoking, and serum CEA levels are known to be elevated in smokers.…”
Section: Discussioncontrasting
confidence: 59%
“…These findings raise the question of whether there is any correlation between serum CEA levels and EGFR gene mutations. It has been reported that there is a positive correlation between serum CEA expression levels and EGFR mutation status in non‐small‐cell lung cancer (NSCLC) patients . However, whether CEA levels are associated with lung tumour genotypes, especially those rare EGFR mutations and ALK gene rearrangements, remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Markers which have been widely used for diagnosing lung cancer include CEA (Yang et al, 2014), Cyfra21-1 (Tomita et al, 2010), NES (Chu et al, 2011), LDH (Ziaian et al, 2014), CRP (Onitilo et al, 2012) and other indexes. However, single marker of lung cancer shows low diagnostic specificity and sensitivity, having poor value for the diagnosis of lung cancer (Leidinger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%